Analysis and Study on Long-Term and Phased Target Values of Soil and Water Conservation Rate in Guizhou Province Based on GIS - LIU Xiaolin; JIN Pingwei; WANG Juan; SHI Yandong; JIANG Xuebing; LUO Yudong; ZENG Xiaolei; KANG Qing (Renmin Zhujiang)
Scientific determination of the target value of soil and water conservation rate in Guizhou Province can provide a supporting basis for the high-quality development of soil and water conservation in Guizhou Province in the new period.Referring to the Guidelines for Determining Soil and Water Conservation Rate Targets formulated by the Ministry of Water Resources,this paper comprehensively considers the actual natural endowment conditions and social and economic development requirements of Guizhou Province and systematically predicts the control situation of water and soil erosion in Guizhou Province in the next 30 years by using the dynamic monitoring data of land use,topography,vegetation, rocky desertification,and water and soil erosion in Guizhou Province and employing the GIS statistical method of spatial superposition.In addition, the long-term threshold of soil and water conservation rate in 2050 and the phased target values in 2025,2030,and 2035 are determined,respectively.The results show that the long-term fully treatable area of soil and water erosion of Guizhou Province is 17 267.06 km2,and the long-term threshold of soil and water conservation rate in 2050 is 83.12%.The phased target values of soil and water conservation rate in 2025,2030,and 2035 are 75.05%,76.74%,and 78.40% respectively.The target value of soil and water conservation rate at each phase is in line with the soil and water conservation planning and the task of water and soil erosion control of Guizhou Province,and it can provide a basis for carrying out soil and water conservation work in Guizhou Province in the new period.